French Language Learning Strategies among BeginnerLevel Learners of a Public University in Central Peninsula Malaysia During Covid-19 - Hamzah Hamsan; Mohd Azidan Abdul Jabar; Hazlina Abdul Halim (Human Resource Management Academic Research Societ, 2024)
International Journal of Academic Research in Progressive Education and Development Volume 12 No. 2 Page (114-123)